(untitled) (Applied Biological Research, 2015)
This study reports the cultivation of arbuscular mycorrhiza (AM), Glomus intraradices spores in Ri-TDNA transformed carrot (Daucus carota) roots using Agrobacterium rhizogenes MTCC culture 532. The germination and mass multiplication of surface sterilized AM spores was studied at different pH levels, sucrose concentrations and inoculumssources. The multiplication of AM spores were successfully established using dual culture technique in modified Strullu and Romands medium amended with 1.0% sucrose at pH 5.5 and incubation temperature of 27°C under condition. The influence of using different inoculum sources such as bunch of spores, infected root bits and spore gel/ agar plug of G. intraradices in root organ culture were evaluated during successive generations under in vitro conditions. Among these, agar plug with high density of viable spores (initially 50) along with few mycorrhized root apexes guarante